(untitled) (Nexo Revista Científica, 2021)
Optimum maintenance of hundreds of thousands of equipment used by each company is one of the main challenges of maintenance, operation, and procurement managers. Continuous production and competition in the business environment and resource constraints require that the vital equipment of each company must be controlled, monitored, and considered. To do this, identifying critical and essential equipment is necessary. In this paper, a formula was defined by field surveys and preferences of 75 petrochemical industry experts and managers to determine the equipment sensitivity index. Experts’ opinions extracted ten compelling features in determining the sensitivity of the equipment, and the weighting coefficient of each one was obtained by using the group decision-making method, Analytical Hierarchy Process. The introduction of the resistive maintenance index formula represents the capability to use strengths and opportunities and sustainability and resistance against weaknesses and threats. The original formula has five sub-indicators consisting of equipment effectiveness, labor effectiveness, cost efficiency, degree of endogeneity, extraversion and exogeneity, and the rate of health, safety, and environmental events. From the perspective of 64 specialists, the group decision-making method and paired comparison matrix were used to determine their weighting coefficient.